Functional Nausea Is Real and Makes You Sick - Di Lorenzo, Carlo (Frontiers in Pediatrics, 2022)
Functional nausea is a condition that severely impairs the quality of life of affected individuals. Only recently, it has been added to the pediatric list of disorders of gut-brain interaction. In most cases, only minimal testing is needed to diagnose functional nausea. Hypnotherapy has been shown to be a very effective treatment and there are several other medical and non-medical interventions which have the potential to benefit sub-groups of patients with chronic nausea.